2012
DOI: 10.1158/1078-0432.ccr-12-0452
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of HER2 Signaling in Human Breast Cancer by Functional Protein Pathway Activation Mapping

Abstract: Purpose Targeting of the HER2 protein in human breast cancer represents a major advance in oncology, but relies on measurements of total HER2 protein and not HER2 signaling network activation. We utilized reverse phase protein microarrays (RPMAs) to measure total and phosphorylated HER2 in the context of HER family signaling to understand correlations between phosphorylated and total levels of HER2 and downstream signaling activity. Experimental Design Three independent study sets, comprising a total of 415 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
102
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 52 publications
4
102
0
1
Order By: Relevance
“…In Western case-series HER2 driven tumors as a group usually have the highest rates of proliferation [23], and Basal-like tumors that are mostly TNBCs, have a tendency to spread early by the hematogenous route without invading the regional nodes [24]. To see whether these patterns were recapitulated in our case series we tabulated the distribution of tumor sub-types into pathological T size groups.…”
Section: Tumor Size and Nodal Involvement In The Subtypes Of Breast Cmentioning
confidence: 99%
“…In Western case-series HER2 driven tumors as a group usually have the highest rates of proliferation [23], and Basal-like tumors that are mostly TNBCs, have a tendency to spread early by the hematogenous route without invading the regional nodes [24]. To see whether these patterns were recapitulated in our case series we tabulated the distribution of tumor sub-types into pathological T size groups.…”
Section: Tumor Size and Nodal Involvement In The Subtypes Of Breast Cmentioning
confidence: 99%
“…These studies show that obtaining nondegraded, full-length proteins from FFPE tissues for multiplex analyses is feasible (27)(28)(29)(30)(31)(32)(33) (41). Other studies have confirmed the validity of this approach and shown that data generated from RPPA analyses of FFPE tissue demonstrate good concordance with traditional immunohistochemistry markers such as HER2 protein in breast cancer (34,40). However, to date, analyses have been performed only for a limited set of protein markers.…”
mentioning
confidence: 74%
“…HER2 phosphorylation (pHER2), considered as the activated state of the receptor, largely coincides with HER2 overexpression (29,30). However, it was found that also a subgroup of HER2-negative tumors express detectable levels of pHER2 that correlate with relatively high HER3 phosphorylation (29).…”
Section: Discussionmentioning
confidence: 99%